Metabolomic Profiling of Dongxiang Wild Rice Under Salinity Demonstrates the Significant Role of Amino Acids in Rice Salt Stress - Chen, Yaling; Huang, Wenxue; Zhang, Fantao; Luo, Xiangdong; Hu, Biaolin; Xie, Jiankun (Frontiers in Plant Science, 2021)
Dongxiang common wild rice is a precious rice germplasm resource for the study and improvement of salt tolerance of rice. The metabolism profile of Dongxiang wild rice under salinity was determined by HPLC-MS to find differential metabolites and screen potential biomarkers for salt-tolerant rice varieties. The global untargeted metabolism analysis showed 4878 metabolites accumulated in seedlings of Dongxiang wild rice (DXWR). Principal component analysis (PCA) and orthogonal partial least squares-discriminant analysis (OPLS-DA) results provided clear metabolism discrimination between DXWR under control and DXWR under salinity. A total of 90 metabolites were significantly changed (49 up-regulated and 41 down-regulated) under salinity, of which the largest increase was DL-2-Aminoadipic acid (27.08 fold), and the largest decrease was L-Carnitine (0.014 fold). Amino acid and nuclear glycosides were mainly up-regulated, while carbohydrates and organics acid were mainly down-regulated in salt-treated group. Among the top ten up-regulated metabolites, five kinds of differential metabolites were amino acids. According to the survival rates of seedlings under salinity, we selected three backcross inbred lines of Dongxiang wild rice with survival rates above 80% as pro-DS and three backcross inbred lines with survival rates below 10% as pro-NDS for amino acid change analysis. The change of L-Asparagine (2.59 fold) was the biggest between pro-DS and pro-NDS under salinity, revealing that the contents of L-Asparagine may be one of the indexes to evaluate the salt tolerance of rice varieties.